Controverion Of Covid 19 Vaccination from Legal Aspects - Yeti Kurniati; Deden Hadi Kushendar (Indonesian Journal of Social Research (IJSR), 2021)
The Covid-19 pandemic is a pandemic that has hit the world, include Indonesia. With this pandemic, Indonesia has experienced an emergency status. Through Presidential Decree No.11 of 2020, Indonesia has announced a health emergency status. With the COVID-19 pandemic, the government has stepped in to make various efforts in order to overcome the impact of the Covid-19 pandemic. The government's effort in overcoming the pandemic is by giving vaccinations to the community in stages. However, in the implementation of the vaccine, the community has not yet understood the benefits of the vaccine, especially considering that the Indonesian people are diverse in culture, various ethnicities, so that in its implementation there are those who are contra but some are pros. Therefore, the existence of this article is one of which is to explain the existence of vaccination in the community which is a right or obligation for society and whether vaccine refusal can be subject to criminal sanctions. This research is a research in the field of law with a research approach that provides a systematic exposure to regulations that regulate certain categories of laws, analyze relationships between regulations, describe areas experiencing obstacles, and even predict future developments with a conceptual approach. The results showed that vaccination was originally the right of everyone. And it also shows that people in society seem to be carried away with emotions to carry out their obligations as citizens who contribute to health for the Indonesian people themselves considering the emergencies in Indonesia today, because people can predict that if they do not participate in vaccination it has the potential to infect and even kill other people. As for punishment, this should be an ultimum remedium, if other institutions such as persuasive methods, socialization and even administrative sanctions related to vaccination are no longer functioning while health emergencies in Indonesia are getting worse